Healthcare costs among patients with chronic constipation: a retrospective claims analysis in a commercially insured population. (February 2014) - Cai, Qian; Buono, Jessica L.; Spalding, William M.; Sarocco, Phil; Tan, Hiangkiat; Stephenson, Judith J.; Carson, Robyn T.; Doshi, Jalpa A.
Abstract Objective: To evaluate total annual all-cause, gastrointestinal-related, and symptom-related healthcare costs among chronic constipation (CC) patients and estimate incremental all-cause healthcare costs of CC patients relative to matched controls. Methods: Patients aged ≥18 years with continuous medical and pharmacy benefit eligibility in 2010 were identified from the HealthCore Integrated Research Database. CC patients had ≥2 medical claims for constipation (ICD-9-CM code 564.0x) ≥90 days apart or ≥1 medical claim for constipation plus ≥1 constipation-related pharmacy claim ≥90 days apart, and no medical claims for irritable bowel syndrome (IBS). Sub-groups with and without abdominal symptoms were classified according to the presence/absence of abdominal pain (ICD-9-CM code 789.0x) and bloating (ICD-9-CM code 787.3x). Controls without claims for constipation, abdominal pain, bloating, or IBS or constipation-related prescriptions were randomly selected and matched 1:1 with CC patients on age, gender, health plan region, and plan type. Generalized linear models with bootstrapping evaluated incremental all-cause costs attributable to CC, adjusting for demographics and comorbidities. Results: Overall, 14, 854 patients (n = 7427 each in CC and control groups) were identified (mean age = 59 years; 75.4% female). Mean annual all-cause costs for CC patients were 11, 991 (2010 USD), with nearly half (44.8%) attributable to outpatient services, including physician office visits and other outpatient services (10.0% and 34.8%, respectively). GI-related costs comprised 33.7% of total all-cause costs. Symptom-related costs accounted for 10.5%, primarily driven by costs of other outpatient services (50.6%). Adjusted incremental all-cause costs associated with CC were 3508 per patient per year (4446 for CC with abdominal symptoms; 2783 for CC without abdominal symptoms), of which 81.0% were from medical services. Incremental cost estimates may be over- or under-estimated due to classification based on claims. Conclusions: CC imposes a substantial burden in direct healthcare costs in a commercially insured population, mainly attributable to greater use of medical services.